“The Great Transformation” and Suicide: Local and Long-Lasting Effects of 1930 Bank Suspensions - Baller, Robert D.; Levchak, Phil; Schultz, Mark (Suicide and Life-Threatening Behavior, 2010)
Depression-era bank suspensions and failures are conceptualized as products of the first part of what Polanyi (1994) called “The Great Transformation,” which involved an imbalanced institutional arrangement in which the economy dominated other institutions. Relying on Durkheim (1897/1951) and Merton (1938, 1968), it is argued that these banking problems accentuated the type of chronic anomie that Durkheim theorized would create normative deregulation and elevated suicide rates over the long-term. Results from county-level analyses are supportive as the 1930 bank suspension rate is positively related to the 2000 suicide rate, controlling for contemporary and historical factors. The mediating roles of integration and chronic anomie are considered, with the latter measured using data from the geocoded General Social Survey.
Keywords: DURKHEIM, Emile; MERTON, Robert; The Great Depression; anomie; countermovement; suicide; suicidology

Neoliberalism and the Biophysical Environment 2: Theorising the Neoliberalisation of Nature - Castree, Noel (Geography Compass, 2010)
There now exists a significant body of theoretically informed empirical research into ‘neoliberal environments’. It comprises numerous studies which together explore the connections between neoliberal principles and policies, on the one side, and the biophysical world on the other. However, making sense of them is by no means straightforward, despite their common focus on neoliberal environments. It is currently left to readers of these studies to synthesise them into a wider, joined-up account of neoliberal environments. This and two companion articles aim for precisely this sort of broad and coherent understanding. The contribution of this second instalment is to present an overarching political economic theory of ‘neoliberal environments’. By synthesising concepts from the work of Karl Marx, Karl Polanyi and James O’Connor, this article presents a framework for thinking about how neoliberal policies relate to the biophysical world.
Keywords: MARX, Karl, 1818-1883; O'CONNOR, James; neoliberal environments

Simultaneous Transitions: Democratization, Neoliberalization, and Possibilities for Class Compromise in South Korea - Kim, Wonik (Review of Radical Political Economics, 2010)
The purpose of this paper is to bring class compromise back into the study of South Korean political economy and present it as a possible alternative to the overwhelmingly one-sided neoliberal trajectory in South Korea. The process and conditions under which positive class compromise is acquired are identified in terms of the Polanyi-Gramsci nexus. This perspective suggests that the restoration of state-led developmentalism would be unfeasible under a democratic regime, while the implementation of a purely neoliberal blueprint may lead to unproductive class conflict. Employing this theoretical framework, I examine possibilities for positive class compromise in the context of the simultaneous transitions—democratization and neoliberalization—in South Korea. JEL classification: B5, H7, O53, P5
Keywords: GRAMSCI, Antonio, 1891-1937; Gramsci; class compromise; democratization; developmental state; neoliberalism

Polanyi's Double Movement and Neoliberalization in Korea and Japan - Kim, Wonik (Social Movement Studies, 2010)
This paper reformulates and extends Polanyi's main insights in The Great Transformations (2001 [1944]) and attempts to theorize the societal countermovement against neoliberalism by illustrating the cases of Korea and Japan. Polanyi's main approach was to synthesize three critical domains: the state, market, and society, and his notion of double movement should be understood as such. Predicated on his double movement, I analytically decompose the mechanism of societal countermovement, emphasizing the importance of social organizations that aggregate people's insecurities and translate them into a political voice capable of acquiring social protection. Applying this analytical framework of the double movement to Korea and Japan reveals that the problem with the conventional understanding of the double movement is that it necessarily arrives at social compensation equilibrium. This paper implies that a highly contentious society, like Korea's, and a highly docile society, like Japan's, may both hinder social welfare provision.
Keywords: Japan; Korea; civil society; civil society organizations; double movement; neoliberalism; social movement studies

Labour as a (Fictitious) Commodity: Polanyi and the Capitalist ‘Market Economy’ - Paton, Joy (The Economic and Labour Relations Review, 2010)
In The Great Transformation, Karl Polanyi problematised the commodity status of labour. He described it as ‘fictitious' and asserted the human aspect of labour necessitates ‘protection’. In bringing Polanyi's mature works to bear on these claims, this article uses the ‘fictitious commodity’ concept to highlight the tension in neoclassical theory between concrete reality and its idealist construction of the economy. This contradiction directly challenges the veracity of the self-regulating market. The article develops two related themes. The first is Polanyi's critique of the neoclassical conception of ‘the economy’ as an ideal (market) construct which gave rise to the notion that labour could be regulated by the forces of supply and demand. The second is the lack of logic in the notion of a ‘self regulating’ market and Polanyi's appreciation of the concrete tendencies of capitalist economies to develop institutional arrangements that ensure the economy is always, and necessarily, more than ‘the market’.
Keywords: capitalist economy; fictitious commodities; fictitious commodity; institutionalisation; labour; laissez-faire; markets; political economy; regulation; self-regulation; social embeddedness

From Pollyanna to the Pollyanna Principle. A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Caspersz, Donella (Global Labour Journal, 2010)
Keywords: BURAWOY, Michael; labor studies; labour studies; pollyanna principle

'False' Optimism: The Key to Historic Breakthroughs? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Clawson, Dan (Global Labour Journal, 2010)
Keywords: BURAWOY, Michael; borderline; global labor studies; global labour studies

From Critical Sociology to Combat Sport? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Webster, Edward (Global Labour Journal, 2010)
Keywords: BURAWOY, Michael; double movement; global labour studies; globalization

Karl Polanyi e a Nova Sociologia Económica: Notas sobre o conceito de (dis)embeddedness - Machado, Nuno Miguel Cardoso (Revista Crítica de Ciências Sociais, 2010)
No contexto da Nova Sociologia Económica, Karl Polanyi é quase consensualmente considerado o “pai” do conceito de incrustação (embeddedness). Todavia, este conceito foi alvo de uma apropriação selectiva por parte da disciplina, sendo negligenciada a sua relação com o restante edifício teórico construído por Polanyi. Pode, com efeito, falar‑se de uma “grande transformação” sofrida pelo conceito de incrustação: se em Polanyi ele está associado a um nível macro(económico) e é utilizado para evidenciar o carácter excepcional da economia capitalista de mercado – que se encontra desincrustada da sociedade –, na NSE, por seu turno, é normalmente associado a um nível meso (e até micro), sendo preconizado que todas as economias – incluindo a capitalista – estão incrustadas. ENG translation: Within the context of New Economic Sociology, Karl Polanyi is almost universally considered the “father” of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the “great transformation” to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy – disembedded from society – in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies – including capitalist economies – are embedded.
Keywords: Karl Polanyi; Nova Sociologia Económica; capitalismo; economia de mercado; economic sociology; embeddedness; incrustação

Decommodification and Egalitarian Political Economy - Vail, John (Politics & Society, 2010)
This article contends that decommodification is an appropriate concept for understanding diverse initiatives such as fair trade, microfinance, open source, social enterprises, and the environmental commons as component features of a common process. Decommodification is conceived as any political, social, or cultural process that reduces the scope and influence of the market in everyday life. Given recent transformations in market societies, a more expansive framework for decommodification is urgently required. Decommodification would insulate non-market spheres from market encroachments; increase the provision of public goods and expand social protection; promote democratic control over the market by creating economic circuits grounded in a logic predicated on social needs rather than profit; and undermine market hegemony by revealing the market’s true social costs and consequences. By ensuring basic needs, enhancing individual capacities and capabilities, and promoting social cooperation and collaboration, decommodification constitutes a central feature of an egalitarian agenda.
Keywords: decommodification; double movement; icy silence; sociology

The Foundation of the Modern National Economy and Discipline over Its Monetary Discourse: A Consideration from the Perspective of Polanyian Economics - Wakabayashi, Shigetaro (Journal of Economic Issues (Taylor & Francis Ltd), 2010)
How does the causality between society and the economy run? After examining this fundamental question from the perspective of Polanyian economics, we conclude that the modern national economy is where bargained exchange is institutionalized by society to pre-exist with the aid of discipline over currency issues. However, this discipline is not provided with a proper institutional defense; and potential fragility of the modern national economy owing to this fact was most vividly revealed by central bankers' conduct in the great liquidity crisis of 2007/8. What are we to do for this?
Keywords: Polanyi's institutionalism; bankers' associations; banking industry - economic aspects; capitalists & financiers; commercial banking system; crises - economic aspects; currency discipline; discourse; discourse and discipline; liquidity (economics); monetary policy; money; negotiation - social aspects; society and the economy

The global financial crisis of 2008–2009: an opportunity for development studies? - Copestake, James (Journal of International Development, 2010)
This paper draws upon the five other papers presented in this volume, along with other presentations made at the 2009 Development Studies Association Conference, to reflect on the relationship between development studies and the 2008–2009 global financial crisis. It first analyses antecedents to the crisis by relating the papers presented by Gore (on long waves of capitalism) and Fischer (on China's integration into the world economy) to a Polanyian analysis. It then considers immediate policy responses with particular reference to India (based on the conference presentation by Mehrotra), China (based on the paper by de Haan) and the 2009 DFID White Paper. Third, it considers two possible additional sources of finance for developing countries: South Korean aid (discussed by Chun et al.) and new forms of international money (discussed by Hudson). The paper concludes that while the crisis is a reminder of structural global economic interconnectedness a challenge for development studies is to combine this fact with analysis that is also interdisciplinary, multi-tiered and policy relevant. Copyright © 2010 John Wiley & Sons, Ltd.
Keywords: 2009 DFID White Paper; China; capitalism; development economics; development studies; global financial crisis; international development; international economic integration

Power and Progress: The Swing of the Pendulum - Stewart, Frances (Journal of Human Development & Capabilities, 2010)
This paper uses Polanyi's 1944 analysis of policy change—in which there are long-term swings from state regulation to markets and back again, as the consequences of one regime lead to political reactions that in turn reverse the policies. It shows how the Polanyi analysis continued to apply throughout the twentieth and early-twenty-first century, well beyond when he wrote, and that the swings also apply to developing country policy-making. It argues that there are new signs of policy change—this time against market domination—in a number of developing countries. The paper concludes that Polanyi's view of the conditions behind policy change—notably long-term political movements, political struggle and political conflict—needs to be introduced into the analysis of policy change for the promotion of human development and the expansion of capabilities.
Keywords: developing countries; government policy; human development; legislation; policy sciences; policy swings; political economy; political planning

Five Theses on the Common - Roggero, Gigi (Rethinking Marxism, 2010)
I present five theses on the common within the context of the transformations of capitalist social relations as well as their contemporary global crisis. My framework involves “cognitive capitalism,” new processes of class composition, and the production of living knowledge and subjectivity. The commons is often discussed today in reference to the privatization and commodification of “common goods.” This suggests a naturalistic and conservative image of the common, unhooked from the relations of production. I distinguish between commons and the common: the first model is related to Karl Polanyi, the second to Karl Marx. As elaborated in the postoperaista debate, the common assumes an antagonistic double status: it is both the plane of the autonomy of living labor and it is subjected to capitalist “capture.” Consequently, what is at stake is not the conservation of “commons,” but rather the production of the common and its organization into new institutions that would take us beyond the exhausted dialectic between public and private.
Keywords: MARX, Karl, 1818-1883; Marxism; capitalism; class composition; cognitive capitalism; common; commons; financialization; model-based reasoning; operaismo; production (economic theory); subjectivity

Globalisation and the Commodification of Labour: Temporary Labour Migration - Rosewarne, Stuart (Economic and Labour Relations Review, 2010)
There has been a qualitative shift in the character of international labour migration with increased temporary labour migration. With circumscribed employment rights, the increased significance of temporary migrant workers underscores arguments that globalisation has engendered a more profound commodification of labour. The instrumentalist approach, especially of international financial institutions in promoting temporary labour migration as a panacea for development, reinforces this impression. Encapsulated in migration-development discourse, labour migration, like other commodities, is presented as a means of generating export revenue for the South. Karl Polanyi's critique of this market-defined construct of labour as a commodity, when labour can only ever be a fictitious commodity, provides a basis for contesting the representation of labour in the migration-development discourse. However, recourse to a Marxist method is held to be essential if we are to move beyond an appreciation of the process in order to interrogate the rationale that is driving the transformation of labour.
Keywords: Marxian; Sraffian; commodification; current heterodox approaches: socialist; fictitious commodities; geographic labor mobility; globalization; immigrant workers; labor migration; labour migration; migrant; migrant workers; migration; value theory

Uncertainty Markets and Carbon Markets: Variations on Polanyian Themes - Lohmann, Larry (New Political Economy, 2010)
Enormous new markets in uncertainty and in carbon have been created recently, ostensibly to enhance the cost-effectiveness of both finance and climate action. In both cases, however, creating the abstract commodity framework necessary to make sense of the notion of 'cost-effectiveness' has entailed losing touch with what was supposedly being costed, helping to engender systemic crisis. The new financial markets expanded credit and multiplied leverage by isolating, quantifying, slicing, dicing and circulating diverse types of uncertainty; the resulting unchecked pursuit of liquidity led to a catastrophic drying up of liquidity. The carbon markets, meanwhile, by identifying global warming solutions with reductions in an abstract pool of tradable pollution rights and linking them with 'offsets' manufactured through quantitative techniques, ended up blocking prospective historical pathways toward less fossil fuel dependence and thus exacerbated the climate problem. Unsurprisingly, both markets have provoked strong, if diverse and confused, movements of societal self-defence. This pattern of action and reaction constitutes a chapter in the political history of commodification as significant in some ways as that describing the movements to commodify land and labour analysed by Karl Polanyi.
Keywords: atmospheric carbon dioxide; cap and trade; carbon credits; carbon offsetting; carbon trading; climate policy; derivatives; emissions trading; financial crisis; greenhouse gas mitigation; offsets

From Polanyi to Pollyanna: The False Optimism of Global Labor Studies - Burawoy, Michael (Global Labour Journal, 2010)
Keywords: EVANS, Peter, 1944-; MARX, Karl, 1818-1883; counter-hegemonic globalization; critique; labor studies; labour studies

The Aporia of Power: Crisis and the Emergence of the Corporate State - Kapferer, Bruce (Social Analysis, 2010)
The argument focuses on the corporate state as an increasingly significant political assemblage that has enabled new configurations of power with related social effects. Here the discussion proceeds from Karl Polanyi's thesis in The Great Transformation. A critical idea that Polanyi pursued related to the state production of economism and individualism, which prepared the ground for the expansion of capital in its globalizing form. The essay develops this idea, indicating that the nationalist capitalism of the state led to a radical change in the political and social orders of states, gradually giving rise to the corporate state assemblage. The emphasis here is on the corporate state as a socio-political order that places radically distinct structural dynamics into impossible conjunction, leading to progressively disastrous social effects concerning poverty and the emergence of new configurations in which war and violence take specific shapes.
Keywords: Great Transformation, The (Book); bureaucratic processes; corporate state; crisis; economism; globalization; individualism; nation-state; poverty; power (social sciences); reterritorialization; violence; war; war machine

Decency in Anglo-American Financial Centres? - Pixley, Jocelyn (Thesis Eleven, 2010)
How can a partial, revisable utopia of 'decent society' be used as a yardstick for assessing today's impersonal forms of social integration? In economic life - this essay's focus - Polanyi's hopes that the 'economic system' might cease 'to lay down the law to society' is a start. Recently, financial firms sold commodified promises and obligations on the allure of democratizing credit and providing financial 'choice' to millions. Yet these 'civilities' exploited people's hopes for a dignified life. Any new, partial utopia (as Keynes's was too - to remove the egregious, humiliating features of 'the society in which we live') is yet to be devised. Maria Markus's concept is useful to ask whether the instrumentalism of macro-economic concepts is a distortion of the institutions of money or intrinsic to them. Could solidaristic compromises through civil society minimize disrespectful relationships embedded in money to create decent institutions?
Keywords: MARKUS, Maria; POLANYI, Karl, 1886-1964; decent economic institutions; economic democracy; economic systems; embeddedness; essay (literary form); financial centres; social integration; utopias

Cultural political economy and critical policy studies - Jessop, Bob (Critical Policy Studies, 2010)
This article introduces cultural political economy as a distinctive approach in the social sciences, including policy studies. The version presented here combines critical semiotic analysis and critical political economy. It grounds its approach to both in the practical necessities of complexity reduction and the role of meaning-making and structuration in turning unstructured into structured complexity as a basis for ‘going on’ in the world. It explores both semiosis and structuration in terms of the evolutionary mechanisms of variation, selection, and retention and, in this context, also highlights the role of specific forms of agency and specific technologies. These general propositions are illustrated from ‘economic imaginaries’ (other types of imaginary could have been examined) and their relevance to economic policy. Brief comments on crisis-interpretation and crisis-management give this example some substance. The conclusion notes some implications for research in critical policy studies.
Keywords: complexity; crisis; crisis-management; cultural political economy; cultural turn; finance-led accumulation; green new deal; neoliberalism

Globalization, Crisis and Social Transformation: A View from the South - Munck, Ronaldo (Globalizations, 2010)
The dominant narrative around the unfolding capitalist crisis is firmly focused on the dominant economies, and in particular the US. This is understandable given that the proximate causes of the crisis lie in the imperial heartlands and crisis resolution measures taken there will have a global impact. But a 'view from the South' is needed to redress the balance and prevent the decimation of global majority likelihoods being presented as mere collateral damage. The first section below tackles the crisis from a global (globalization) perspective emphasizing its impact in the South and what that it might mean in terms of political prospects. I then go on to develop a hybrid Karl Polanyi/Antonio Gramsci theoretical lens on counter-movements based on their writings responding to the last systemic capitalist crisis in the 1930s. Finally, I turn to the ways in which the international labour movement and the subaltern or post-colonial worlds are contesting the terrain vacated by unregulated market capitalism. As Gramsci would say the old is dying but the new has not yet been born. La narrativa dominante alrededor de la crisis capitalista revelada, esta firmemente enfocada a las economias dominantes, y particularmente E.E.U.U. Esto es comprensible, dado que las proximas causas de la crisis yacen en la region central imperial y las medidas de resolucion de la crisis que se tomaron alli tendran un impacto global. Pero se necesita un 'punto de vista desde el sur' para compensar el equilibrio y prevenir la devastacion de las posibilidades de las mayorias globales presentadas como simple dano colateral. La primera seccion abajo trata la crisis desde una perspectiva global (globalizacion), enfatizando su impacto en el sur y lo que eso puede significar en terminos de prospectos politicos. Luego procedo con el desarrollo de una lente teorica hibrida de Karl Polanyi/Antonio Gramsci sobre movimientos opuestos en base a sus escritos que responden a la ultima crisis capitalista sistemica en la decada de 1930. Finalmente, vuelvo a las maneras en las cuales el movimiento laboral internacional y los mundos subalternos o postcoloniales estan disputando el terreno vacio por el mercado capitalista sin regulacion. Como Gramsci diria, lo viejo se esta muriendo, pero lo nuevo no esta aun por nacer. [image omitted]
Keywords: GRAMSCI, Antonio, 1891-1937; South; capitalism; countermovement; crisis; financial crises; financial crisis; globalization; hegemony; international markets; labour; post-colonial; social change; transformation

L’Encastrement Social des Marchés. Éléments théoriques et empiriques pour une analyse en termes de réseaux relationnels - Plociniczak, Sébastien (Revue de la régulation. Capitalisme, institutions, pouvoirs, 2010)
Despite the core role played by market in economic theoretical frameworks, the market is still little addressed and finally remains a vague type at best equivoque. This thesis aims to contribute to a collective pattern devoted to the diversification of market analysis since the 70s. This collective pattern is the New Economic Sociology, founded and built on a central idea, i.e. the embeddedness. In the perspective of Karl Polanyi and Mark Granovetter’s works, the thesis intends thus to enlighten first the use of this idea as the necessary clarification does not occur until now. Then, it puts forward the fact that an analysis of markets may definitely benefit from a deeper understanding of the multilateral logic of relational networks. At last, on the base of main assumptions defined in this thesis, the robustness of the heuristic contractual model of the Transaction Costs Economics depicted by Oliver E. Williamson is assessed.
Keywords: capital social; contrat; coûts de transaction; embeddedness; encastrement; forme hybride; institutions; marchés; réseaux relationnels; social capital

An Australian international political economy? The high road and the low road - Leaver, Richard (Australian Journal of International Affairs, 2010)
Drawing on Karl Polanyi's distinction between formal and substantive theory, this article argues that 'an Australian international political economy' could (and should) be erected on the historical study of Australia's substantive articulations with the global economy.
Keywords: Australia; economic policy; international economic relations; international relations; policy sciences

Hannah Arendt et Karl Polanyi : le libéralisme économique, l'effondrement du politique et la société de masse, Abstract - Azam, Geneviève (Revue du MAUSS, 2010)
RésuméDans les années 1930, Hannah Arendt et Karl Polanyi ont partagé l’expérience du déracinement, de la désolation et celle de l’effondrement de la civilisation du xixe siècle. À partir de l’analyse de la société de marché pour K. Polanyi et de la condition de l’homme moderne pour H. Arendt, ils montrent comment l’économisme et la construction d’une société économique au xixe siècle, sont à l’origine de l’avènement de la société de masse qui porte des tendances totalitaires. Leur regard croisé donne des clés de compréhension des menaces qui pèsent qui pèsent sur nos « sombres temps »., In the 1930s, H. Arendt and K. Polanyi shared the experience of rootlessness and the collapse of nineteenth century civilisation. Through the analysis of the market society (K. Polanyi) and the condition of modern man (H. Arendt), they analyse how economicism and the advent of an economic society in the nineteenth century have engendered mass societies which carry totalitarian tendencies. This double perspective gives some keys to understand the threats of our « dark times ».
Keywords: ARENDT, Hannah; economic liberalism; mass society

D/developments after the Meltdown - Hart, Gillian (Antipode, 2010)
Part of what makes the current conjuncture so extraordinary is the coincidence of the massive economic meltdown with the implosion of the neoconservative Project for a New American Century, and the reappearance of US liberal internationalism in the guise of “smart power” defined in terms of Diplomacy, Development, and Defence. This essay engages these challenges through a framework that distinguishes between “Development” as a post-war international project that emerged in the context of decolonization and the Cold War, and capitalist development as a dynamic and highly uneven process of creation and destruction. Closely attentive to what Gramsci calls “the relations of force at various levels”, my task in this essay is to suggest how the instabilities and constant redefinitions of official discourses and practices of Development since the 1940s shed light on the conditions in which we now find ourselves.
Keywords: GRAMSCI, Antonio, 1891-1937; US hegemony; United States; capitalism; capitalist crisis; development; economic development; essay (literary form); hegemony; militarism

A British Bureaucratic Revolution? Autonomy Without Control, or "Freer Markets, More Rules." - Le Galès, Patrick; Scott, Alan (Revue Française de Sociologie, 2010)
This paper addresses a puzzle: how to account for changes in the routine behavior of groups, organizations and individuals in Britain? Following a detailed analysis of state-market interdependence and the role of the state in creating the market, an analysis drawn from the thinking of Weber and Polanyi, we suggest adapting Weber's notion of bureaucratic revolution: in what we call the British bureaucratic revolution, the state has played an essential role in social change by creating institutions and rules that are lastingly reorienting actors' behavior. The example of the healthcare field is examined in order to identify the specific mechanisms that have been impacting on behavior within an approximately ten-year period; namely, the introduction of 1) competitive practices (sanction/reward) and 2) auditing and inspection. If this interpretation is valid, then it is reasonable to assume that the effects of this bureaucratic revolution extend beyond Britain.
Keywords: Great Britain; bureaucracy; medical care; revolutions; social change

Now and Then - Watts, Michael J. (Antipode, 2010)
Antipode was launched into the firmament of the 1970s. We might reflect upon how well the journal and its contributors fully appreciated the historical gravity and weight of what was surrounding the project to create “a radical journal of geography”. What sort of radicalism was on offer? The language was “social relevance” from “a radical (Left) political viewpoint”. In writing to celebrate Antipode's birthday, this time in another, and similar, firmament there is still the need to confront the challenge of radicalism and its meanings. Whether we agree with Perry Anderson that the last vestiges of the 1960s have been finally swept away, that the “fluent vision” of the Right has no equivalent on the Left and that embedded liberalism is now as remote as “Arian bishops”, where do radical alternatives stand in relation to the fractured hegemony of neoliberalism? At the very least the need for alternatives is more pressing than ever. David Harvey has proposed rethinking the idea of “the right to the city”. But what other rights might we rethink? I reflect upon this question by returning to the 1960s and 1970s and Marxist debates over the law, and by thinking about the possibilities offered by this Polanyian moment.
Keywords: ANDERSON, Perry; Magna Carta; Marxist philosophy; Polanyi moment; Polanyian moment; common law - history; commons; essay (literary form); law; law - political aspects; markets; radicalism; scholarly periodicals

Who decides what is fair in fair trade? The agri-environmental governance of standards, access, and price - Bacon, Christopher M. (The Journal of Peasant Studies, 2010)
The agri-environmental governance of value chains can favour a Polanyian double movement seeking social protection and control over price setting markets or it can advance a neoliberal logic that strives to overcome the few remaining civic and ecologic obstacles to full market dominance. Coupled with a typology that contrasts corporate social responsibility and social economy Fair Trade models, this theoretical framework elucidates positions in the current policy debates about the minimum coffee price standard. Many Southern smallholders consider Fair Trade's standards, which for coffee include direct market accesses for smallholder cooperatives, minimum prices, and environmental criteria, among the best deals available. The smallholder empowerment benefits are often better than competing eco-labels. However, this study finds that Fair Trade minimum prices lost 41 percent of their real value from 1988 to 2008. Despite objections from several ‘market driven’ firms and national labelling initiatives, smallholders' collective advocacy and this research contributed to the Fairtrade Labelling Organisations International's (FLO) decision to mandate a 7–11 percent minimum price increase. The price debates demonstrate that Fair Trade governance is neither purely neoliberal nor social movement led – it is a highly contested socially embedded practice. Voices without votes, North–South inequalities, and dwindling prices paid to its stated protagonists indicate the need for governance reform, cost of living price adjustments, and additional investment in the innovative alternative trade and hybrid models.
Keywords: double movement; eco-labels; environmental and agricultural governance; environmental science; environmental studies; fair trade; peasant studies; standards; sustainability

Crisis, Continuity and Change: Neoliberalism, the Left and the Future of Capitalism - Castree, Noel (Antipode, 2010)
Abstract:  This essay's point of departure is the coincident economic and environmental “crises” of our time. I locate both in the dynamics of capital accumulation on a world-scale, drawing on the ideas of Marx, Karl Polanyi and James O’Connor. I ask whether the recent profusion of “crisis talk” in the public domain presents an opportunity for progressive new ideas to take hold now that “neoliberalism” has seemingly been de-legitimated. My answer is that a “post-neoliberal” future is probably a long way off. I make my case in two stages and at two geographical scales. First, I examine the British social formation as currently constituted and explain why even a leading neoliberal state is failing to reform its ways. Second, I then scale-up from the domestic level to international affairs. I examine cross-border emissions trading—arguably the policy tool for mitigating the very real prospects of significant climate change this century. The overall conclusion is this: even though the “first” and “second” contradictions of capital have manifested themselves together and at a global level, there are currently few prospects for systemic reform (never mind revolution) led by a new, twenty-first century “red-green” Left.
Keywords: Britain; European Union; climate change; economic crisis; emissions trading; environmental crisis; social formation

Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire - Servet, Jean-Michel (Revue Tiers Monde, 2010)
English translation: Karl POLANYI has an indirect understanding of the societies that were part of the Third World in the fifties. From anthropologists he came out with the principle of reciprocity. He then opposed this principle of economic integration to both redistribution and market principles. Reciprocity can neither be viewed as a practice of primitive societies (as in evolutionist approaches) nor as a gift and counter-gift exchange. Reciprocity needs to be understood as a social whole and through a claimed mutual dependency. In this approach, reciprocity allows to set up the definition of the solidarity-based economy. Jean-Michel Servet, “ Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire ”, Revue Tiers Monde 2/2007 (n° 190) , p. 255-273
Keywords: reciprocity

Is the Globalization Consensus Dead? - Wade, Robert (Antipode, 2010)
The development economist Dani Rodrik recently declared that “the globalization consensus is dead”. The claim has momentus implications, because this consensus has steered economic policy around the world for the past quarter century. It emanates from the heartland of neoclassical economics, and defines the central tasks of the Washington-based organizations which claim to speak for the world. This essay answers two main questions. First, is Rodrik's claim true, and by what measures of “consensus”? Second, to the extent that the consensus has substantially weakened, is the state returning to the heart of economic life, as Karl Polanyi might have predicted? The answers? First, the globalization consensus about desirable economic policy has weakened, though it is far from “dead”. Second, the western state is returning to the heart of economic life in response to the current global economic crisis, but will retreat soon after national economies recover—because unless the crisis becomes a second Great Depression, the norms of more free markets and more global economic integration will be politically challenged only at the margins. New rules of finance may be introduced, but with enough loopholes that by 2015 Wall Street and the City will operate in much the same way as in the recent pre-crisis past.
Keywords: Washington consensus; catch-up growth; financial crisis; globalization consensus; income distribution; pension funds; poverty

The Making of Karl Polanyi's Economic Sociology. (In Japanese. With English summary.) - Wakamori, Midori (History of Economic Thought, 2010)
The main purpose of this paper is to understand Polanyi's research project after The Great Transformation. This includes his developing ideas on economic history and theory of economic institutions after 1947, when he came to Columbia University in New York. This paper deals mainly with Polanyi's new agenda, namely "the place of the economy in society" in the intellectual context of post World War II United States of America.
Keywords: Marxist; Sraffian; economic anthropology; economic sociology; history of economic thought since 1925: socialist; history of economic thought: individuals; social and economic stratification

Polanyian meditations on economy and society: a review of 'Market society: the great transformation today' - Dale, Gareth (Dialectical anthropology, 2010)
Keywords: book review; cultural ethnography; economic anthropology; market economy; society

Au-dela de la dichotomie marche-institutions: L'institutionnalisme de Douglass North face au defi de Karl Polanyi. (With English summary.) - Didry, Claude; Vincensini, Caroline (Revue Francaise de Socio-economie, 2010)
On the basis of the "challenge" North (1977) identified in the works of Polanyi, we propose to outline the originality of North's institutionalism, especially in comparison with "new institutionalism" in economics as well as in sociology. Far from endorsing the dichotomy between market and non market dimensions of economic activities at the basis of the analyses of Williamson and Granovetter, North's definition of institutions as "rules of the game" allows him to conceive of institutions as the institutional foundations of the market and therefore as explanatory principles of historical dynamics.
Keywords: Austrian; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought since 1925; institutional

Movement, Countermovement, and Investment Rules - Schneiderman, David (Conference Papers -- Law & Society, 2010)
This paper examines the extent to which one manifestation of neoliberal transnational legality, represented by the investment rules regime, may be vulnerable to critical resistance in the post-recession environment. If the regime was experiencing a crisis of legitimacy before the global recession set in, it might now be portrayed as having broken down entirely. This paper argues, in contrast, that the regime has a constitution-like resiliency that is intended to adapt and last far beyond the present unsettled global scene. First, for many states in the global South, there is no possibility of a Polanyian countermovement without an influx of needed capital from sources such as international financial institutions or foreign investors. This has the effect of locking states further into the regime's web of disciplines. Second, international investment tribunals have been reflexive agents and have responded to legitimacy problems raised by state and social movement actors by adjusting their interpretation of investment treaty disciplines. It turns out that, as Foucault warned, everything is dangerous - states and social movements must move carefully as they proceed to navigate through the current conjuncture. ..PAT.-Unpublished Manuscript
Keywords: Global South; countermovement; global south; investment rules regime; investment tribunals; neoliberal transnational legality

Fair Trade and the Double Movement: The Promise and Contradictions of Improving Labor Standards in the Global South via Market Mechanisms - Shorette, Kristen (Journal of Workplace Rights, 2010)
I examine Fair Trade (FT) as a social movement that emerges as a regulative force in response to the rise of neoliberalism. I apply Polanyi's (1944, 1957) classic concepts of embeddedness and the double movement to understand the conflict that arises within a coherently motivated social movement. Using interview and participant observation data along with content analysis of FT organization mission statements, this research examines the role of conflict within the FT movement over how best to improve the well-being of producers in the global South. I discuss the different, conflicting ways in which FT participants think about improving labor conditions in the global South and the inherent conflict in using market mechanisms to counter market forces. I conclude that while participants share the values of human rights, equality, and environmentalism, realizing these goals through concrete market activities reveals the tension between the benefits of liberalizing and the benefits of regulating the production and sale of FT goods that may impede the continued growth of the movement.
Keywords: developing countries; double movement; embeddedness; fair trade; human rights; labor laws & legislation; labour laws & legislation; neoliberalism; production standards; social movements; unfair competition; workplace rights

Local Food: A Social Movement? - Starr, Amory (Cultural Studies/Critical Methodologies, 2010)
This article analyzes the development of “local food” institutions from a social movements perspective. Over the last decade, institutions that “shorten the links” between producer and consumer have developed through a diverse collaboration of many social sectors (farmers, agronomic experts, retailers, chefs, food writers, and several distinct consumer sectors). Some agronomists and rural sociologists critical of the globalization and industrialization of agriculture have recognized this development as heralding Polanyian “reembedding” of market exchanges in social relations. This article analyzes whether and how local food is a social movement, using new social movement theory as an analytic framework.
Keywords: community-based economics; local food; local foods; localism; organic food; organic foods; social change; social movements; social psychology

Fair Trade Banana Production in the Windward Islands: Local Survival and Global Resistance - Torgerson, Anna McLoughlin (Agriculture and Human Values, 2010)
Fair trade banana farming in the Windward Islands of the Caribbean has emerged since the late 1990s in response to a crisis. Rulings by the World Trade Organization ended a longstanding trade dispute between the US and the EU by eliminating a system of preferential access of Windward Island bananas to the UK market. What followed was a period of rapid decline in banana exports from these small islands and a widespread abandonment of banana cultivation. Those banana farmers who remain are now primarily fair trade producers. Fair trade banana production in the Windward Islands can thus be conceived as a survival strategy that farmers have developed in response to a particular instance of neoliberal globalization. The paper considers this response especially in the context of recent fieldwork on the island of St. Vincent. In light of contributions by several scholars who have drawn upon the work of Polanyi to understand both fair trade and resistance to neoliberalism, fair trade banana production in the Windward Islands appears significant not only as a local survival strategy, but also as part of a larger countermovement that resists neoliberal globalization.
Keywords: agriculture in international trade; economic development: agriculture; energy; environment; international trade organizations; micro analysis of farm firms, farm households, and farm input markets Q12; natural resources; other primary products; trade policy

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
Keywords: classical Greek economy; economic history; embeddedness

The Rise and Fall of the Market Economy - Zaman, Asad (Review of Islamic Economics, 2010)
The core economic functions of production and distribution of goods can be handled by many different methods. After the fall of communism, the market mechanism has become nearly universal. Conventional economic theories argue that this is natural, because it is the best and the most efficient method for organizing economic affairs in a society. This paper, based on the analysis of Polanyi (1944) and Klein (2008) argues that the opposite is true. Market mechanisms conflict with natural mechanisms for production and exchange in traditional societies. Unregulated markets cause tremendous damage, as can be witnessed today in terms of countless economic crises, wars, environmental destruction, as well as damage to social networks. Because of this damage, market societies can only be maintained by force, as well as disinformation. To resolve crises on myriad fronts caused by the unregulated market, it is the need of the hour to find viable alternatives.
Keywords: capitalist systems: performance and prospects; comparative analysis of economic systems; cultural economics: religion; other economic systems: performance and prospects

The Role of the State in Making a National Market: The Evolution of the Grain Market in China (1978-2000) - Zhou, Wubiao (China Agricultural Economic Review, 2010)
The paper aims to examine Karl Polanyi's view of market evolution in the context of the emergence of a national grain market in China's transition economy. The dataset used includes information about inter-provincial grain trade on China's grain market from November 1999 to October 2000. A priori blockmodelling method is used for hypothesis testing. This paper finds that a partially integrated national grain market had emerged at the beginning of the twenty-first century in China in spite of local protectionism. Additionally, the emergence of this market is found to be partly a result of the reform-oriented state's attempt to create national wholesale grain markets.
Keywords: agricultural policy; agriculture; agriculture: aggregate supply and demand analysis; collectives; communes; economic development: agriculture; energy; environment; food policy; natural resources; other primary products; prices